2013
DOI: 10.1016/j.amjmed.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Waist Circumference, Physical Activity, and Risk of Hearing Loss in Women

Abstract: BACKGROUND Acquired hearing loss is highly prevalent, but prospective data on potentially modifiable risk factors are limited. In cross-sectional studies, higher body mass index (BMI), larger waist circumference, and lower physical activity have been associated with poorer hearing, but these have not been examined prospectively. METHODS We examined the independent associations between BMI, waist circumference and physical activity and self-reported hearing loss in 68,421 women in the Nurses’ Health Study II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
149
3
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(166 citation statements)
references
References 61 publications
(75 reference statements)
6
149
3
8
Order By: Relevance
“…For example, recent studies have reported that higher BMI and larger waist circumference were related to an increased risk of hearing loss [5]. A study of adolescents aged 12-19 years found a relationship between obesity and higher hearing thresholds at all frequencies [6].…”
Section: Introductionmentioning
confidence: 98%
“…For example, recent studies have reported that higher BMI and larger waist circumference were related to an increased risk of hearing loss [5]. A study of adolescents aged 12-19 years found a relationship between obesity and higher hearing thresholds at all frequencies [6].…”
Section: Introductionmentioning
confidence: 98%
“…It has been shown in previous studies that compared with hearing loss diagnosed by audiogram, self-reported hearing loss is a relatively reliable indicator of hearing loss (22)(23)(24)(25). In addition, significant associations between other factors and risk of self-reported hearing loss have been observed using this method of assessment in NHS I and NHS II (14,(26)(27)(28)(29).…”
Section: Ascertainment Of Hearing Lossmentioning
confidence: 76%
“…These factors included age (1); race (1); body mass index (27,30); waist circumference (27); alcohol consumption (28,31); intakes of folate (32), β-carotene (29), trans fatty acids, omega-3 fatty acids (33), β-cryptoxanthin (29), vitamin A, vitamin B 12 , vitamin C (29), vitamin E, potassium (34), and magnesium (35); physical activity level (27,36); smoking (31); diabetes (37); hypertension (26); and tinnitus (38,39).…”
Section: Ascertainment Of Covariatesmentioning
confidence: 99%
“…3 Obesity related atherosclerosis may lead to stiffening and constriction of the internal auditory artery and reduction in cochlear blood flow. 8 Reduced blood supply to cochlea, whether due to micro-vascular or macrovascular compromise, can lead to capillary constriction within the stria vascularis, cell death, and poorer hearing sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…2 Acquired hearing loss is a highly prevalent disabling chronic condition, which can impair communication, social interaction, and adversely affect psychosocial well-being and quality of life. 3 Therefore identification of potentially modifiable risk factors for hearing loss is a compelling public health goal.…”
Section: Introductionmentioning
confidence: 99%